Beneficial Effects of Exercise on Depression and Anxiety During the Covid-19 Pandemic: A Narrative Review - Hu, Shaojuan; Tucker, Lorelei; Wu, Chongyun; Yang, Luodan (Frontiers in Psychiatry, 2020)
First reported in Dec 2019, the on-going COVID-19 pandemic has become a public health emergency of international concern (PHEIC). The isolation and quarantine implemented during the COVID-19 pandemic limited the physical and social activities of the population, which contributed to an increased prevalence of mental disorders. Depression and anxiety are the most common mental illnesses conferring a serious impact on individuals’ life quality. This review summarizes the mental health consequences of COVID-19, especially regarding depression and anxiety. Exercise as an intervention for anxiety and depression has been demonstrated in both animal studies and human clinical trials. The underlying mechanisms include regulation of the production of brain-derived neurotrophic factor (BDNF), D-β-hydroxybutyrate, synaptic transmission, hypothalamic pituitary adrenal (HPA) axis, tryptophan hydroxylase, GSK3β/β-catenin pathway, neuroinflammation, oxidative stress, and the PGC-1α1-PPAR axis. In addition, we summarized exercise strategies to fight against anxiety and depression according to the information from American College of Sports Medicine (ACSM), World Health Organization and recent literatures about physical exercise during COVID-19.